'Overpaid' and 'inefficient': print media framings of the public sector in The Irish Times and The Irish Independent during the financial crisis. - Marron, Aileen (Critical Discourse Studies, 2019)
Using a frame analysis approach this paper examines how The Irish Times and the Irish Independent portrayed public sector workers during Ireland's economic crisis. Using a sample of coverage from 2009 and 2010 it discusses the five media frames identified in this analysis, three of which were hegemonic and two of which were counter hegemonic. In this paper, I argue that coverage of the public sector by each newspaper was imbalanced and inaccurate. This paper also finds that both newspapers were strong advocates of austerity cutbacks in the public service as a solution to Ireland's financial crisis, frequently representing this idea as 'fact' while simultaneously delegitimising those opposing this viewpoint.